The case against assisted suicide : for the right to end-of-life care - Foley, Kathleen M., 1944-; Hendin, Herbert (Johns Hopkins University Press, 2002)
"Few issues are as volatile or misunderstood as physician-assisted suicide and euthanasia. In The Case against Assisted Suicide: For the Right to End-of-Life Care, Drs. Foley and Hendin unravel why such principles as patient autonomy, compassion, and rationality, which are often invoked by supporters of legalization, fail to address the actual situations of terminally ill patients. Incisive discussions by leading authorities in the fields of medicine, law, and bioethics from the United States and abroad provide compelling multidisciplinary perspectives and discussions on what is at stake at the end of life. Several chapters present the risks that legalization of assisted suicide poses to some of society's most vulnerable groups, particularly those who are elderly, are depressed, or have physical disabilities. The authors provide in-depth analyses of the actual practice of assisted suicide in places where it is legally sanctioned. The Case against Assisted Suicide spells out what the medical profession needs to do to improve palliative care. It also thoughtfully and persuasively indicates the changes in social policy necessary to develop a more humane response to the complex issues facing terminally ill patients."--Jacket